Korelasi Konsentrasi Etanol 5% Pada Bahan Bakar Gasolin Terhadap Performa, dan Emisi Gas Buang Mesin Bensin 150cc - Syarifudin, Syarifudin; Yohana, Eflita; Muchammad, Muchammad; Suhartana, Suhartana; Fatkhurrozak, Faqih; Lukman Sanjaya, Firman; Qurohman, M. Taufik (P3M Politeknik Negeri Cilacap, 2023)
Ethanol has higher octane and oxygen properties than fossil-fuel gasoline. Along with the increase in gasoline dependency and exhaust emissions, the use of ethanol as a fuel is urgently studied. This study aimed to observe the concentration of 5% ethanol in gasoline on the performance and exhaust emissions of a 150cc gasoline engine that was operated at 1000, 2000, and 3000rpm. The observation results show that the concentration of 5% ethanol in gasoline correlates with an increase in performance with indications of an increase in EGT, Brake power, BTE, and a decrease in SFC. On the emission side, it is also correlated with an increase in the quality of exhaust emissions with indications of increased CO2 emissions and reduced CO and HC emissions. The best correlation of 5% ethanol concentration was obtained at an operating speed of 2000rpm with an increase in EGT of 10.70%, an increase in Brake power of 9.49%, an increase in BTE of 38.62%, an increase in CO2 emissions of 23.06%, a decrease in SFC of 26 .49%, CO emission reduction of 16.67%, and HC emission reduction of 4.24%.